Effects of ionizing radiation on the human body - Patrycja Ręba (Kazimierz Wielki University, 2019)
Admission All living organisms on Earth are constantly pierces ionizing radiation. It's the kind of radiation that during the passage through mattergenerates ions having electric charge. Ionizing radiation occurring in its natural form can also be dangerous to the human body, and its large doses may even lead to death. Natural radiation is at all times present in the human environment, which is caused everywhere occurring radioisotopes of various elements in nature, and cosmic radiation. The level of influence of ionizing radiation on the body also depends on the size of the absorbed dose and the type of body tissue and the phase of the cells. Most promienioczułymi are reproductive cells, hematopoietic and lymphoid tissue. High radiosensitivity have also the deepest layer of the skin, the eye lens, the intestinal mucosa endothelia vessels, and cartilage cells and (osteoblasts). Goal The aim of the study was to analyze the impact of ionizing radiation on the human body. Material and methods In order to obtain the necessary information has been analyzed information, data and reports on the impact of ionizing radiation on the human body. Results In the literature one can find the distribution of the effects of irradiation of ionizing distinguishing the effects of stochastic and deterministic. For stochastic effects proIonizing radiation is given to those whose instance is defined in a probability, that they may but need not occur. Mostly, it is assumed that the indicated probability depends exponentially from the resultinghuman dose. Among the effects of stochastic stands out above all cancers, but also hereditary changes in the offspring.Stochastic effects can be divided into somatic and genetic. Somatic effects take place mainly insomatic cells and comprise only one body. In contrast, genetic effects manifest themselves mostly in the germ cells and cause changes in successive generations.And the second type of effects of ionizing radiation or deterministictic They occur when a person receives a relatively large doses, which can provide temporary or permanent tissue damage. It should be emphasized that in the case of exposure to very high doses of radiation can lead to so-called. radiation sickness, which may result in death. Conclusions As evidenced by now taken action by mankind, and especially the production of artificial radiation can be achieved olbrzbare improvement in both the treatment and medical diagnostics, and also contributed to a number of techniques in scientific research, agriculture and industry, which have improved the conditions of life on earth. The effects of radiation are examined over a freshto. The international community, through organizations such as the International Commission on Radiological Protection, United Nations Scientific Committee. Effects of Atomic Radiation and the International Atomic Energy Agency, Established strict limits on the doses of radiation applications, transportation and disposal of nuclear waste, and also oversees whether nuclear energy is used only for peaceful purposes.